Quantitative Analysis of HAADF–STEM Images of MoVTeTaO M1 Phase Catalyst for Propane Ammoxidation to Acrylonitrile. Issue 22 (16th July 2015) - Woo, Jungwon; Borisevich, Albina; Koch, Christoph; Guliants, Vadim V.
Abstract: High‐angle annular dark‐field scanning transmission electron microscopy (HAADF–STEM) image simulations were performed to determine accurate metal distributions in the MoVTeTaO M1 phase catalyst for propane ammoxidation. QSTEM simulation, based on a multislice method with the frozen phonon approximation, was chosen because of the excellent agreement between experimental and simulated HAADF–STEM images. This simulation method successfully provided accurate metal distributions in the MoVTeTaO M1 phase and indicated significantly lower V occupancies of the linking sites 1, 2, 3, 4, and 7, and higher Ta occupancy in site 9 than the previously reported metal occupancies. This novel methodology for accurate HAADF–STEM image analysis is a valuable tool for accurate analysis of local chemical compositions in a wide range of ordered catalytic materials. Abstract : Exact distribution : Quantitative scanning transmission electron microscopy simulation yields accurate metal distributions in the MoVTeTaO M1 phase catalyst for propane ammoxidation. Left) experimental HAADF–STEM image of the M1 phase catalyst; Right) simulated HAADF–STEM images of the M1 structure model.